PROSES PENGHUNIAN KAMPUNG PRINGGONDANI - Ikhwanuddin Ikhwanuddin (Universitas Negeri Yogyakarta, 2005)
ABSTRACTThis research aims to reveal how the forming process of Pringgondanikampong, Catur Tunggal, Depok, Sleman, Jogjakarta province. The Pringgondanikampong is a densely populated kampong in the Gajah Wong's river bank thatcan be categorize as an urban viilage or city's kampong. The forming process ofthis area is attractive object to be researched, because of the status of this landas tanah kas desa (the property of village administration) borrowed as the rightsof rented farming land. In other side, this research aims to explore the drivenfactors that influencing the inhabitation process that forming this settlement.The fenomenological method was used as method of research. Thismethods require unseperation between researcher and object of research. Theobject of research is observed without separation of it context. The informationhad been collected from the trusted informan then it was conformed to user orresponder. The trusted informan are old people or the people who settle in thiskampong erlier so their knowledge about kampong are assumed much morethen the others. Trusted informan and responder is elected by purposive manner.The instruments of research are log book, pen, survey map and researcher.This research reveal the process of settlement in this Pringgondani kampongthat can be seen by two sight: the first as a process of exchange of rented landright and the second as a process of attending of inhabitant. The factorsinfluencing process of inhabitation are: status of land, unproductive land condition,recognition of village administration about this functional area as settlement,demand of rented room, and self-improvement of inhabitant.Keywords: process of inhabitation, rented land right, urban village